Getting the Most out of Social Media: Creating a Social Media Plan - Lauri M. Baker; Caroline R. Warwick; Jessica C. Fernandez; Joy Rumble (EDIS)
This 3-page publication on how to create a social media plan is part of the Getting the Most out of Social Media series, created for Florida professionals, business owners and individuals interested in understanding how to strategically use social media. The following sections will outline how to develop a plan to successfully adopt and maintain social media platforms for agriculturalists and Extension personnel. Minor revision by Lauri Baker, Caroline Warwick, Jessica Fernandez, and Joy Rumble.